2022
DOI: 10.3389/fimmu.2022.976011
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell transfusions impact response rates to immunotherapy in patients with solid malignant tumors

Abstract: Red blood cell (RBC) transfusions have been shown to exert immunosuppressive effects in different diseases. In consequence, RBC transfusions might also negatively influence the response to immunotherapeutic treatment approaches. To address how RBC transfusions impact response rates of antitumor immunotherapy (IT), we conducted a retrolective clinical study of patients with different solid tumors treated with IT (atezolizumab, pembrolizumab, nivolumab and/or ipilimumab). We assessed the number of RBC concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The current hypothesis that explains the biological association between blood components and poorer oncological outcomes is that transfusion-related immunomodulation (TRIM) acts as a propagating factor for the TH2 immune response, favoring a pro-tumoral environment through inhibition of interleukin (IL)-2 and stimulation of suppressor T cells, allowing tumor spread and recurrence[ 20 - 22 ]. The recent application of immunotherapy in gastrointestinal tract cancers provided additional data by demonstrating that TRIM could be acting as an opponent and negatively impacting its effectiveness and survival[ 32 ]. Another important topic related to the immune response is the data provided by Lange et al [ 33 ] that showed no difference in using leukocyte depletion in long-term survival, underlining that specific constituents of allogeneic blood may mediate the TRIM effect.…”
Section: Discussionmentioning
confidence: 99%
“…The current hypothesis that explains the biological association between blood components and poorer oncological outcomes is that transfusion-related immunomodulation (TRIM) acts as a propagating factor for the TH2 immune response, favoring a pro-tumoral environment through inhibition of interleukin (IL)-2 and stimulation of suppressor T cells, allowing tumor spread and recurrence[ 20 - 22 ]. The recent application of immunotherapy in gastrointestinal tract cancers provided additional data by demonstrating that TRIM could be acting as an opponent and negatively impacting its effectiveness and survival[ 32 ]. Another important topic related to the immune response is the data provided by Lange et al [ 33 ] that showed no difference in using leukocyte depletion in long-term survival, underlining that specific constituents of allogeneic blood may mediate the TRIM effect.…”
Section: Discussionmentioning
confidence: 99%
“…Transfusions have demonstrated a positive impact on solid organ transplant outcome, a negative one on cancer dissemination and relapse, and on RR to checkpoint inhibitors in solid cancers. 20 , 22 , 43 Transfusion may thus impair CAR T-cell fitness and lead to an increased relapse rate, although this hypothesis needs to be further explored. Finally, prolonged cytopenia can predispose for significant infectious complications, which is the main driver of NRM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the administration of RBC transfusions after the initiation of immunotherapy (IT) treatment, seems to have a detrimental impact on the response rates to immunotherapy. Therefore, recent studies advocate for a conservative approach to transfusion management in patients undergoing immunotherapy [57].…”
Section: Discussionmentioning
confidence: 99%